Overcoming the Challenges in Implementing Type 2 Diabetes Mellitus Prevention Programs Can Decrease the Burden on Healthcare Costs in the United States - Kritika Subramanian; Inuka Midha; Vijaya Chellapilla (Journal of Diabetes Research)
Theoretically, identifying prediabetics would reduce the diabetic burden on the American healthcare system. As we expect the prevalence rate of prediabetes to continue increasing, we wonder if there is a better way of managing prediabetics and reducing the economic cost on the healthcare system. To do so, understanding the demographics and behavioral factors of known prediabetics was important. For this purpose, responses of prediabetic/borderline diabetes patients from the most recent publicly available 2015 Behavioral Risk Factor Surveillance System (BRFSS) survey were analyzed. The findings showed that there was a correlation between household income, geographic residence in the US, and risk for developing diabetes mellitus type 2, aside from the accepted risk factors such as high BMI. In conclusion, implementation of the National Diabetes Prevention Program is a rational way of reducing the burden of DM on the healthcare system both economically and by prevalence. However, difficulties arise in ensuring patient compliance to the program and providing access to all regions and communities of the United States. Technology incorporation in the NDPP program would maintain a low-cost implementation by the healthcare system, be affordable and accessible for all participants, and decrease economic burden attributed to diabetes mellitus.